Precipitation Hardenable High Entropy Alloy for Tooling Applications. (22nd February 2019) - Stryzhyboroda, O.; Hecht, U.; Witusiewicz, V. T.; Laplanche, G.; Asabre, A.; Wilms, M.B.; Weisheit, A.
ABSTRACT: We present a high entropy alloy (HEA) from the system Al-Co-Cr-Fe-Ni with small additions of W, Mo, Si and C which was designed to allow for precipitation hardening by annealing in the temperature range from 600 to 900 ° C. The alloy development was supported by thermodynamic computations using ThermoCalc software and the specimens were produced by arc melting. The microstructure of one selected sample in as-cast and annealed conditions was analysed using SEM/EDS, SEM/EBSD and TEM. The as-cast microstructure consists of spinodally decomposed BCC dendrites enveloped by FCC+Cr23 C6 eutectic. Upon annealing at 700 ° C for 24 h nanoscale precipitates form within the spinodal BCC as well as from FCC. Precipitation is exquisitely uniform leading to an increase in microhardness from 415 HV0.5 in the as-cast state to 560 HV0.5 after annealing. We investigated coarsening of this microstructure using varying holding time for a constant temperature of 700 ° C. The microstructure evolution during coarsening and the corresponding mechanical properties obtained from instrumented indentation experiments are presented in this work.